Tingkat Kepuasan Pasien terhadap Pelayanan Kefarmasian - Herianto Bangun; Rulia Meilina (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Quality pharmaceutical services can improve patient adherence to treatment and contribute to optimal therapeutic outcomes. This study aims to describe the level of patient satisfaction with pharmaceutical services. This study is quantitative research with descriptive, observational, and cross-sectional designs. This research was conducted in Permata Saribudolok from January to March 2025. The research population consists of all patients who visit for treatment at Klinik Permata Saribudolok. The study's sample size was 47 patients obtained through a simple random sampling technique. The inclusion criteria for the research sample may include patients who have received treatment, have complete data at Klinik Permata Saribudolok, and are willing to participate in the research activities throughout the study period. The research variable includes the level of patient satisfaction. Data were collected through questionnaires to measure patient satisfaction levels. Data processing and analysis were conducted descriptively to calculate the frequency distribution of each variable studied. The research results show that patients who are satisfied with the appearance of pharmacy staff amount to 80.9%, reliability to 76.6%, responsiveness to 72.3%, empathy to 87.2%, and assurance aspects to 78.7%. In conclusion, most patients are satisfied with all aspects of pharmaceutical services.